Ammonium recycling supports toxic Planktothrix blooms in Sandusky Bay, Lake Erie: Evidence from stable isotope and metatranscriptome data - Hampel, Justyna J.; McCarthy, Mark J.; Neudeck, Michelle; Bullerjahn, George S.; McKay, Robert Michael L.; Newell, Silvia E. (Harmful algae, 2019)
•Planktothrix blooms in Sandusky Bay relied on regenerated NH4+ in late summer.•Summer regeneration provided bioavailable N equivalent to 77% of annual N load.•Planktothrix was N-starved and mobilized intracellularly stored N in late summer.•Planktothrix in Sandusky had higher NH4+ affinity than Microcystis in Maumee Bay. Sandusky Bay, Lake Erie, receives high nutrient loadings (nitrogen and phosphorus) from the Sandusky River, which drains an agricultural watershed. Eutrophication and cyanobacterial harmful algal blooms (cyanoHABs) persist throughout summer. Planktothrix agardhii is the dominant bloom-forming species and the main producer of microcystins in Sandusky Bay. Non-N2 fixing cyanobacteria, such as Planktothrix and Microcystis, thrive on chemically reduced forms of nitrogen, such as ammonium (NH4+) and urea. Ammonium regeneration and potential uptake rates and total microbial community demand for NH4+ were quantified in Sandusky Bay. Potential NH4+ uptake rates in the light increased from June to August at all stations. Dark uptake rates also increased seasonally and, by the end of August, were on par with light uptake rates. Regeneration rates followed a similar pattern and were significantly higher in August than June. Ammonium uptake kinetics during a Planktothrix-dominated bloom in Sandusky Bay and a Microcystis-dominated bloom in Maumee Bay were also compared. The highest half saturation constant (Km) in Sandusky Bay was measured in June and decreased throughout the season. In contrast, Km values in Maumee Bay were lowest at the beginning of summer and increased in October. A significant increase in Vmax in Sandusky Bay was observed between July and the end of August, reflective of intense competition for depleted NH4+. Metatranscriptome results from Sandusky Bay show a shift from cyanophycin synthetase (luxury NH4+ uptake; cphA1) expression in early summer to cyanophycinase (intracellular N mobilization; cphB/cphA2) expression in August, supporting the interpretation that the microbial community is nitrogen-starved in late summer. Combined, our results show that, in late summer, when nitrogen concentrations are low, cyanoHABs in Sandusky Bay rely on regenerated NH4+ to support growth and toxin production. Increased dark NH4+ uptake late in summer suggests an important heterotrophic contribution to NH4+ depletion in the phycosphere. Kinetic experiments in the two bays suggest a competitive advantage for Planktothrix over Microcystis in Sandusky Bay due to its higher affinity for NH4+ at low concentrations.